Mechanical performance and global warming potential of unaged warm cup lump modified asphalt - Abdulrahman, S. (Elsevier Ltd, 2021)
The use of natural rubber modified bitumen to improve pavement performance exist over a century. However, few documented research explore its mechanical performance in warm mix asphalt (WMA). This paper examined the rutting, moisture damage, tensile properties and carbon emission of cup lump rubber modified asphalt (CMA) in hot mix asphalt (HMA) and WMA. Aggregate coating and compactability tests were employed to select the production temperature of the WMA. The result shows that the warm cup lump modified asphalt (WCMA) has excellent rutting resistance of less than 2 mm rut depth at 8000 load repetitions representing 21 improvement compared with the conventional HMA. The tensile property was improved by 62 due to cup lump rubber (CLR) modification. Moisture damage evaluation shows that the WCMA retained more than 95 bitumen coating and has a tensile strength ratio (TSR) value of 99, thus fulfilling the AASHTO T283 minimum requirement of 80. The asphalt mixtures resistance to severe condition of stripping and rutting happening simultaneously revealed that the mixes are more sensitive to rutting than the stripping component of the APA-moisture damage test. The emission test result shows that producing WCMA at 40 Â°C lower than CMA reduced 5 kg of CO2 equivalent, amounting to 23 reduction in global warming potential. The multi-attribute analysis combined the mechanical performance results and environmental impact to rank WCMA as the optimum mixture for future road construction. Â© 2021 Elsevier Ltd